Visuospatial working memory in young adults and in children with learning difficulties - Garcia, Ricardo Basso (2013)
Visuospatial working memory (VSWM) comprises specialised subsystems devoted to storage of visual features and spatial locations. Recently, research has been focused on understanding feature binding in memory and how bound objects are temporarily held in working memory. In the current thesis we have addressed two broad questions: What is the nature of bound visual representations in working memory? Is there a specific deficit in binding in individuals with learning difficulties? In Study 1, young adults were required to recall locations, objects and object-location bindings under visual or spatial concurrent task conditions. A clear double dissociation pattern was observed: movement discrimination mainly disrupted location memory, whereas colour discrimination mainly disrupted object memory. Such selective interference was also observed for object-location memory, suggesting that bound object representations depend on the updating of specific feature information. In Study 2, two groups of children with specific learning disabilities dyslexia and nonverbal learning disability (NLD) were compared to typically developing children in three tasks that required forward and backward recall of locations, colours, and colour-location bindings. Only children with NLD have impairments in memory for locations and colours, especially in backward recall of locations, and there were no group differences for the colour-location binding task. The patterns seen in recall of locations and colours separately were no longer present when these features had to be recalled together, suggesting the specificity of binding processes. Finally, in Study 3, two groups of children at-risk of learning disabilities (verbal and nonverbal) were compared to typically developing children in VSWM for colours, shapes, and shape-colour bindings. It was observed that memory for shape-colour binding is impaired in both groups at risk of learning disabilities, whereas memory for either shapes or colours are spared. This provides further support that problems in memory binding may be widespread across different populations with learning difficulties and atypical development. In summary, taken together, our results are in line with an associative view of binding, i.e., bound object representation results from associative links between different types of features. VSWM seems to operate on both feature- and object-level information.